Why Corporate Social Responsibility Isn't a Piece of Cake - Marques, José; Mintzberg, Henry (MIT Sloan Management Review, 2015)
Relying on the familiar clichés - "doing well by doing good," finding "win-win solutions" and being a "good corporate citizen"--Accomplishes little in the bigger scheme of things. In fact, these platitudes sometimes encourage corporate social irresponsibility.